2021
DOI: 10.3390/su13169110
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Production Mix in the Agricultural Machinery Industry Considering Sustainability in Decision Making

Abstract: Competition among companies is growing globally, with the need to increase productivity and efficiency in the product sector. However, there is also a growing concern about global warming and the depletion of natural resources, as well as their effects on human health. In this context, all human activities that involve intense usage of resources must take into account sustainability as one of the decision criteria. This work presents the application of decision-making methods to define the best product mix in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Naturally, if successful, small-town economic development will continue on its own and may even help raise regional income. Agrotourism is all tourism-related activities that educate visitors about the agriculture industry's production methods and turn rural areas into destinations where they may directly consume agricultural products (Hoose et al 2021). In addition, local farmers may have the opportunity to boost their revenue and improve their living conditions with the growth of agrotourism (Swastika et al 2017).…”
Section: Follow-ups Must Be Made In the Mangrove Empowerment Project ...mentioning
confidence: 99%
“…Naturally, if successful, small-town economic development will continue on its own and may even help raise regional income. Agrotourism is all tourism-related activities that educate visitors about the agriculture industry's production methods and turn rural areas into destinations where they may directly consume agricultural products (Hoose et al 2021). In addition, local farmers may have the opportunity to boost their revenue and improve their living conditions with the growth of agrotourism (Swastika et al 2017).…”
Section: Follow-ups Must Be Made In the Mangrove Empowerment Project ...mentioning
confidence: 99%
“…Hu et al [40] used the ANP (analytic network process) and BSC (balanced scorecard) methods in order to develop a network of machinery maintenance for agricultural production. Hoose et al [41] used the AHP and DEA (data envelopment analysis) methods to select tractor-trailers for grain transportation. Lu et al [42] used the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method to select suppliers for new agricultural machinery for the development of agricultural production.…”
Section: Selection Of Tractors In Agriculturementioning
confidence: 99%
“…It was observed that cost was considered the most important of the criteria, while the environmental impact was the least important criterion in all comparisons. It is worth noting that some recent studies point to greater weight for the environmental criterion, suggesting that the weights attributed by experts must be influenced by the current situation owing to the coronavirus disease pandemic (Hoose et al, 2021). Table…”
Section: Application Of Ahp To Optimized Beamsmentioning
confidence: 99%